The utility of custom-developed tooth extraction simulator - A comparative analysis from beginner to trainer. Issue 1 (January 2021) - Sugahara, Keisuke; Bessho, Hiroki; Nishiyama, Akihiro; Koyama, Yu; Koyachi, Masahide; Toyoda, Tomoaki; Kasahara, Kiyohiro; Watanabe, Akira; Takano, Masayuki; Katakura, Akira
Abstract: Objective: In clinical dentistry, tooth extraction is one of the most fundamental techniques learned during mandatory dentist clinical internships. However, there are fewer opportunities for students to perform this procedure on actual patients. Hence, a tooth extraction simulator was developed based on clinical experience to evaluate the appropriate load and magnitude of the three- dimensional forces (x, y, and z axes) applied while using forceps for tooth extraction. Methods: Twenty-three subjects were divided into five groups according to experience (i.e., fifth-year dental students, clinical intern dentists, early-career oral surgeons, board-certified members of the Japanese Society of Oral and Maxillofacial Surgeons [JSOMS], and JSOMS specialists and clinical instructors). The simulator was developed with Osada Electric Co. Ltd. using electromagnets and load cells. The magnitude of the three-directional load applied in actual tooth extractions was used as basis for the simulator. Results: With increasing clinical experience, a consistent trend in terms of lower variation in loading, stable initial movements, and low directional variability was observed. On determination of the appropriate standards from the measurements of this study, users can not only gauge the amount of force needed to grasp the teeth and tear the periodontal ligament by dislocation but also appreciate the orientation and force required for tooth extractions. Conclusion: This study demonstrated the utility of a tooth extraction simulator in evaluating the generated loads and movements during tooth extraction procedures.